DETERMINATION OF COORDINATES OF THE BASIC POINTS OF THE ILLUMINATED PART OF THE SPHERICAL PLANET'S VISIBLE DISC - Mikhalchuk, V. V. (Одеські астрономічні публікації, 2017)
The formulae for determination of planetocentric coordinates of the basic points of an illuminated part of the visible disc of a spherical planet in projection onto the plane of the sky are derived. The formulae are deduced from general expressions using an auxiliary coordinate system connected with equator of intensity, and realizing the transition from this system to planetocentric coordinates. The proposed formulae do not require attraction of auxiliary coordinate system and allow a immediate transition, in planetocentric coordinates, from the center of the geometric disc of the spherical planet to the given point of its visible disc under various conditions of illumination. The planetocentric coordinates of the basic points for visible discs of the Mercury, Venus and Mars on their physical ephemerides are calculated.